ОСНОВНІ НАПРЯМКИ ВЗАЄМОДІЇ МІЖ СУДОВО-ЕКСПЕРТНИМИ УСТАНОВАМИ В УКРАЇНІ - Контимирова, Вікторія Вікторівна (SUPREMANCE OF LAW, 2019)
The article emphasizes that due to the lack of legal order of interaction betweenforensic institutions, it is important to develop specific areas of interaction between forensic institutions in Ukraine. The main areas of such interaction are the following: direct examinations, research, scientific and methodological, preventive, informational work. It is pointed out that the allocation of specific areas of interaction betweenforensic institutions is a necessary factor in their well-established and purposeful cooperation not only in conducting joint (comprehensive) expert research, but also in addressing pressing issues arising from the direct activities of forensic institutions and implementation of public relations in this area.